2006
DOI: 10.1300/j229v07n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Services and Sexual Abuse: The Need for Staff Training

Abstract: Identification of child abuse by mental health services is important for formulation of the causes of presenting problems and for development of comprehensive treatment plans. A small but growing number of studies suggest, however, that the majority of child sexual abuse cases are not identified by mental health services. A similarly small literature also suggests that abuse survivors are extremely reluctant to spontaneously tell anyone about the abuse, indicating that professionals have a responsibility to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 53 publications
7
56
1
1
Order By: Relevance
“…A New Zealand study of 252 women who had been sexually abused during childhood found that 52% waited at least 10 years to tell someone, and 28% had told nobody . In another New Zealand study, of 191 women who had received counselling for childhood sexual abuse, the average time taken to tell anyone about it was 16 years (Read et al, 2006d).…”
Section: Waiting To Be Told?mentioning
confidence: 99%
See 1 more Smart Citation
“…A New Zealand study of 252 women who had been sexually abused during childhood found that 52% waited at least 10 years to tell someone, and 28% had told nobody . In another New Zealand study, of 191 women who had received counselling for childhood sexual abuse, the average time taken to tell anyone about it was 16 years (Read et al, 2006d).…”
Section: Waiting To Be Told?mentioning
confidence: 99%
“…A survey of New Zealand women who had been sexually abused during childhood and were later treated by mental health services found that 63% had never been asked about childhood sexual abuse by mental health staff (Read et al, 2006d). These studies focus on sexual and physical abuse, but neglect and emotional abuse may be similarly unrecognised by mental health services (Thompson & Kaplan, 1999).…”
Section: Askingmentioning
confidence: 99%
“…have been systematically incorporated into archival records. However, such meticulous methods may not be standard in all inpatient or outpatient facilities (Read [16]). Thus, the reliability and other types of validity (e.g., concurrent and divergent validity) of the five subtypes of child abuse in SMI should be replicated in other clinical settings in order to examine whether under-investigation is an issue.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing child abuse histories with accuracy is one of the most challenging tasks in psychiatric rehabilitation [16]. Even though there is evidence that self-reports of child sexual abuse or child physical abuse among individuals with first-episode psychosis had a fair level of agreement in the presence or absence of child abuse documented in case notes [17], it is still unclear whether psychiatric patients at various phase of illness accurately report or under-report child abuse during inpatient intake interviews [17][18][19], and the literature varies in regard to reported temporal stability of the reported abuse [17,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation